Specific Features of Boron Detection and Interpretation in High-Entropy Borides and B₄C-Based Composites: A Brief Review - Zaulychnyy, Yaroslav; Mosiak, Vasyl; Biriukovych, Lina; Stepanov, Oleg; Bogomol, Iurii (Physics and Chemistry of Solid State, 2026)
The specific features of detecting and interpreting boron distribution in composite materials based on boron carbide and high-entropy borides are considered. Literature data on the use of EDS and WDS methods for studying elemental distribution in high-entropy borides and B₄C–(TiZrHfNbTa)B₂ composites are analyzed. It is shown that the intensity of boron B Kα radiation strongly depends on the local chemical composition of the material and may significantly decrease in regions enriched with metallic components. It has been established that one of the reasons for this effect is the absorption and scattering of X-ray radiation by heavy elements, primarily zirconium, whose M₄,₅ absorption edge energy is close to the energy of the boron B Kα band. As a result, regions with reduced signal intensity may appear on boron distribution maps; however, these regions do not indicate the absence of boron in the studied crystallites. The obtained results demonstrate the need to take into account the specific interaction of characteristic radiation with the components of multicomponent boride systems when interpreting X-ray spectral analysis data.